Student Information System (online course registration system) / Har Wai Keong - Har , Wai Keong (2000)
This Student Information System (SIS) will be developed with the objectives of utilizing the computer and Information technology to provide an easy and converuent online course registration system for the Faculty of Computer Science and Information Technology. This system promises a new dimension, which transcends across time and space. Time and space no longer are barriers. Students can register their courses at a different location and at a different time zone. SIS is a web-based application that uses to keep track of students' information. SIS consists of two sections that are student section and administrator section. Student section will be developed using Active Server Pages and scripting language technologies. Students' tasks will be implement on the web that enables them to register their courses online through Internet. Meanwhile, the administrator section w-ill be developed using Visual Basic 6.0 as a non web-based application. The purposes are to maintain a secure environment and reduce processing time. This section will provide the administrator with facilities to control the registration process. The system also manages to do checking and validation on the students' registration, which will reduce enormously the administrator workloads. SIS is a stand-alone system. It will be developed on the Microsoft Windows NT Server 4.0 platform utilizing database that will be created and stored from Microsoft SQL server. Internet Information Server will be used as web server while Visual InterDev 6.0 will be used as a tool for designing dynamic web application for this project. It is believed that the system will gradually become an essential to everyone in the future.